2016
DOI: 10.1021/acs.jpca.6b08868
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate Ion Availability at the Air–Water Interface

Abstract: Amphiphilic organic compounds at the air−water interface play key roles in the nucleation, growth, and aging process of atmospheric aerosol. Surface-active species are expected to react preferentially with atmospheric oxidants, such as the OH radical, at the air−water interface via specific mechanisms. Establishing the relative availability of the different amphiphilic species to gas-phase oxidants at the air−water interface under atmospherically relevant conditions is, however, challenging. Here we report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 87 publications
8
51
0
Order By: Relevance
“…The underlying process is genuinely interfacial, because γ(NO2)e is significantly enhanced by cationic surfactants, weakly depressed by anionic surfactants, and unaffected by hydrophobic 1-octanol. [44][45][46][51][52] Significantly, our results are consistent with the γ(NO 2 ) e ∼ 10 -4 values measured on ∼3 mM NaCl droplets in a cloud chamber, [53][54] a finding that remained unexplained vis-à-vis the γ(NO2)w < 1 × 10 -7 value previously measured on pure water, and consequently ignored by the atmospheric chemistry community. In short, in the presence of dense aerosols, such as those that develop in urban smog at noon, reaction R2 can become competitive with the photolysis of NO 2 (g), R3:…”
Section: The Disproportionation Of Nitrogen Dioxide On Aqueous Aerososupporting
confidence: 90%
“…The underlying process is genuinely interfacial, because γ(NO2)e is significantly enhanced by cationic surfactants, weakly depressed by anionic surfactants, and unaffected by hydrophobic 1-octanol. [44][45][46][51][52] Significantly, our results are consistent with the γ(NO 2 ) e ∼ 10 -4 values measured on ∼3 mM NaCl droplets in a cloud chamber, [53][54] a finding that remained unexplained vis-à-vis the γ(NO2)w < 1 × 10 -7 value previously measured on pure water, and consequently ignored by the atmospheric chemistry community. In short, in the presence of dense aerosols, such as those that develop in urban smog at noon, reaction R2 can become competitive with the photolysis of NO 2 (g), R3:…”
Section: The Disproportionation Of Nitrogen Dioxide On Aqueous Aerososupporting
confidence: 90%
“…times smaller than those at m/z 431 (and 433) from OA at [1-octanol] = [OA] = 100 mM reveals that 1-octanol is much less reactive than OA toward CIs, although both species are expected to have similar affinities for aqueous surfaces. 25,32,43,[69][70] The C 23 ethers and esters produced in each case, by having similar mass and structures (see This finding is in line with gas-phase reaction rate constants of CIs + HCOOH/CH 3 COOH, which approach collisionally controlled values: k ≥ 10 -10 cm 3 molecule -1 s -1 , 22 vs. the much smaller values for CIs + methanol/2-propanol. 48,50,68 Tobias and Ziemann have reported that rate constants of gas-phase C 13 CIs reactions with various species increase in the order: water < methanol < 2-propanol < formaldehyde < formic acid < heptanoic acid, over a 10 4…”
Section: Page 3 Of 23 Acs Paragon Plus Environmentsupporting
confidence: 64%
“…31 Previous experiments in our laboratory have demonstrated that mass spectral signal intensities are proportional to interfacial ion populations. [31][32]36 We have shown that mass spectra: (1) are not affected by the weak local electric fields at the tip of the grounded nozzle, [37][38] (2) correspond to species generated by reactions taking place in the outermost interfacial layers of the microjets. 29,[31][32][39][40] The limited exposures of unambiguously identified by the characteristic M/M+2 = 3/1 signal ratios arising from natural abundance 35 Cl: 37 Cl::0.75:025 isotopes.…”
Section: Page 3 Of 23 Acs Paragon Plus Environmentmentioning
confidence: 99%
“…This was demonstrated by the well-defined RCOO − (R = n-alkyl) mass signals versus pH titration curves (inflection points at pK a (RCOOH) = 4.8) obtained from aqueous RCOOH solutions [14,37,38,[41][42][43][44][45]. Well-defined pK a (RCOOH) = 4.8 titration curves imply that the sampled layers have well-defined proton activities [46].…”
Section: Products Of Gas-liquid Reactions Are Mainly Formed On Liquidmentioning
confidence: 87%